2006
DOI: 10.1097/01.ccm.0000199067.71968.6e
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent influence of barbiturates but not of propofol on human leukocyte phagocytosis of viable Staphylococcus aureus

Abstract: Our in vitro model points at substantially different effects of barbiturates and propofol on phagocytosis of S. aureus, which is one of the most important pathogens in patients who need neuroprotective therapy. The inhibitory effects of both barbiturates demonstrate a strong dose-dependency, with more pronounced effects for methohexitone. Impairment of phagocytosis activity was more pronounced than granulocyte recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…The effect of propofol on phagocytosis has not been clear. Some investigators have reported that propofol inhibits phagocytosis in neutrophils and macrophages in vitro (11,30), and others described no effect of propofol on human leukocyte phagocytosis (42).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of propofol on phagocytosis has not been clear. Some investigators have reported that propofol inhibits phagocytosis in neutrophils and macrophages in vitro (11,30), and others described no effect of propofol on human leukocyte phagocytosis (42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pentobarbital directly enhanced the viabilities of cells, and protected cells from apoptosis induced by deferoxamine mesylate-induced hypoxia. Further, in an in vitro model substantially different effects of barbiturates and propofol were found on phagocytosis of Staphylococcus aureus [126]. The inhibitory effects of barbiturates demonstrated a strong dose-dependency.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, high-dose barbiturates have numerous, potentially life-threatening, adverse effects [6,7]. Complications may include prolonged iatrogenic coma, even after cessation of the infusion; hypotension as a consequence of venous pooling, peripheral vasodilatation, and impaired myocardial contractility [8,9]; respiratory depression [10]; severe electrolyte and endocrine disturbances [11,12]; and immunosuppression with frequent nosocomial infections [13][14][15]. We present here a case demonstrating that an exacerbating factor may, in some cases, be the accumulation of propylene glycol, the vehicle used to administer intravenous pentobarbital and phenobarbital.…”
Section: Introductionmentioning
confidence: 99%